The Environmental, Social, and Governance information creates value for the shareholder in the Portuguese Stock Exchange? - Rosário, J.; Arraiano, I.G.; Annes, M.C. (7th International Conference on CSR, Sustainability, Ethics and Governance, 2021)
The relationship between financial performance and sustainability has been investigated in developed countries applying different methodologies. However, this type of study has not been carried out in the Portuguese listed companies. This study investigates the impact of the three sustainability pillars, Environmental, Social, and Governance (ESG) information on the price of assets listed on the Portuguese stock exchange over the period 2002-2020. Applying different models, the results show us that the investors do not react to the sustainability information and do not significantly value the three pillars of ESG sustainability, but market positively values environmental practices in listed Portuguese companies.